The Public Library Catalogue as a Social Space: A Case Study of Social Discovery Systems in Two Canadian Public Libraries - Spiteri, Louise F.; Tarulli, Laurel (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper uses transaction log data to examine how library users interact with two social discovery systems used in two Canadian public library systems. Results indicate that user-generated content is not used extensively or significantly in the two social discovery systems. Format is the predominant facet used to refine searches; the remaining facets are significantly underrepresented. Cette étude utilise les journaux transactionnels pour déterminer comment les usagers des bibliothèques interagissent avec deux systèmes de découverte sociaux en place dans deux réseaux de bibliothèques publiques canadiennes. Les résultats indiquent que le contenu généré par les utilisateurs n’est pas utilisé à grande échelle ou de façon importante dans aucun des deux systèmes de découverte sociaux. Le format est la principale facette utilisée pour raffiner les recherches; les autres facettes étant sous-représentées.